Mitochondrial Complex I Inhibitors and Forced Oxidative Phosphorylation Synergize in Inducing Cancer Cell Death - Roberta Palorini; Tiziana Simonetto; Claudia Cirulli; Ferdinando Chiaradonna (International Journal of Cell Biology)
Cancer cells generally rely mostly on glycolysis rather than oxidative phosphorylation (OXPHOS) for ATP production. In fact, they are particularly sensitive to glycolysis inhibition and glucose depletion. On the other hand mitochondrial dysfunctions, involved in the onset of the Warburg effect, are sometimes also associated with the resistance to apoptosis that characterizes cancer cells. Therefore, combined treatments targeting both glycolysis and mitochondria function, exploiting peculiar tumor features, might be lethal for cancer cells. In this study, we show that glucose deprivation and mitochondrial Complex I inhibitors synergize in inducing cancer cell death. In particular, our results reveal that low doses of Complex I inhibitors, ineffective on immortalized cells and in high glucose growth, become specifically cytotoxic on cancer cells deprived of glucose. Importantly, the cytotoxic effect of the inhibitors on cancer cells is strongly enhanced by forskolin, a PKA pathway activator, that we have previously shown to stimulate OXPHOS. Taken together, we demonstrate that induction in cancer cells of a switch from a glycolytic to a more respirative metabolism, obtained by glucose depletion or mitochondrial activity stimulation, strongly increases their sensitivity to low doses of mitochondrial Complex I inhibitors. Our findings might be a valuable approach to eradicate cancer cells.